Combining end-user recruitment methods for usability testing of eTriage Service - Marja Helmi Ylilehto; Eini Saarivesi; Jarmo Reponen; Pia Liljamo (Finnish Social and Health Informatics Association, 2019)
The Finnish national eHealth and eSocial strategy emphasizes citizens' active role in promoting their own well-being by improving information management and implementing self-management and online services. In the Emergency Hub, part of the Finnish online health portal (Health Village), an eTriage Service is being developed by ICT experts and healthcare professionals. To make the eTriage Service available to the public, the user interface must comply with relevant quality and safety regulations. The aim of this paper is to describe the recruitment methods used for eTriage Service usability testing and the feasibility of those methods. The results of the actual usability testing are not discussed in this article. Two different recruiting methods were combined: online recruiting with remote testing and organized on-site testing occasions. A total of 219 volunteer end-users were recruited and 115 (52.5%) of them performed the usability testing. A better participation rate was achieved with organized on-site testing occasions, but the method consumed significantly more time and effort on the part of developers. A sufficient number and variety of end-users were recruited by combining different recruiting methods. Online recruiting with remote usability testing helps reduce the costs and effort of developers but may require a longer period of time to achieve a sufficient number of testers. A complex or highly novel, self-performing test process without any support might affect negatively the number of testers available by the online recruitment. It also seems that usability testing for digital health services can be more attractive to healthcare professionals than to persons with no healthcare education background.